Original sin - Di Novi, Denise; Guinzburg, Kate 1962-.; Lees, Carol; Cristofer, Michael; Banderas, Antonio; Jolie, Angelina 1975-.; Jane, Thomas; Thompson, Jack.; Itzin, Gregory; Mackie, Allison; Pringle, Joan.; Richards, Cordelia; et al. ([Los Angeles, Calif.] MGM Home Entertainment, 2002)
A mysterious woman from Boston whose insatiable lust for her new wealthy, plantation owner husband is exceded only y her desire for his fortune.
Title from container.
Originally produced as a motion picture in 2001.
Based on the novel "Waltz into darkness" by Cornell Woolrich.
"Distributed in the Philippines by Viva Video Inc."--Container.
Executive producers, Sheldon Abend, Ashok Amritraj, David Hoberman ; director of photography, Rodrigo Prieto ; editor, Eric Sears ; music, Terence Blanchard.
Antonio Banderas, Angelina Jolie, Thomas Jane, Jack Thompson, Gregory Itzin, Allison Mackie, Joan Pringle,Cordelia Richards.
Keywords: Man-woman relationships -- Drama; Plantations -- Cuba -- Drama; Fortune hunters -- Drama; Feature films